Fibroblast-Specific Genetic Manipulation of p38 Mitogen-Activated Protein Kinase In Vivo Reveals Its Central Regulatory Role in Fibrosis. Issue 6 (8th August 2017) - Molkentin, Jeffery D.; Bugg, Darrian; Ghearing, Natasha; Dorn, Lisa E.; Kim, Peter; Sargent, Michelle A.; Gunaje, Jagadambika; Otsu, Kinya; Davis, Jennifer
Abstract : Background: In the heart, acute injury induces a fibrotic healing response that generates collagen-rich scarring that is at first protective but if inappropriately sustained can worsen heart disease. The fibrotic process is initiated by cytokines, neuroendocrine effectors, and mechanical strain that promote resident fibroblast differentiation into contractile and extracellular matrix–producing myofibroblasts. The mitogen-activated protein kinase p38α ( Mapk14 gene) is known to influence the cardiac injury response, but its direct role in orchestrating programmed fibroblast differentiation and fibrosis in vivo is unknown. Methods: A conditional Mapk14 allele was used to delete the p38α encoding gene specifically in cardiac fibroblasts or myofibroblasts with 2 different tamoxifen-inducible Cre recombinase–expressing gene–targeted mouse lines. Mice were subjected to ischemic injury or chronic neurohumoral stimulation and monitored for survival, cardiac function, and fibrotic remodeling. Antithetically, mice with fibroblast-specific transgenic overexpression of activated mitogen-activated protein kinase kinase 6, a direct inducer of p38, were generated to investigate whether this pathway can directly drive myofibroblast formation and the cardiac fibrotic response. Results: In mice, loss of Mapk14 blocked cardiac fibroblast differentiation into myofibroblasts and ensuing fibrosis in response to ischemic injury or chronic neurohumoral stimulation. A similar inhibition of myofibroblast formation and healing was also observed in a dermal wounding model with deletion of Mapk14 . Transgenic mice with fibroblast-specific activation of mitogen-activated protein kinase kinase 6–p38 developed interstitial and perivascular fibrosis in the heart, lung, and kidney as a result of enhanced myofibroblast numbers. Mechanistic experiments show that p38 transduces cytokine and mechanical signals into myofibroblast differentiation through the transcription factor serum response factor and the signaling effector calcineurin. Conclusions: These findings suggest that signals from diverse modes of injury converge on p38α mitogen-activated protein kinase within the fibroblast to program the fibrotic response and myofibroblast formation in vivo, suggesting a novel therapeutic approach with p38 inhibitors for future clinical application. Abstract : Supplemental Digital Content is available in the text.